2000
DOI: 10.1016/s1201-9712(00)90073-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtypes of the HLA-DR antigens in pulmonary tuberculosis

Abstract: Results suggest that the presence of HLA-DRB1*16 alleles may increase the risk of development of PTB, whereas HLA-DRB1*13 alleles may be resistant to tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 39 publications
1
34
1
1
Order By: Relevance
“…DRB1*16 is reported to have a positive association with the susceptibility to tuberculosis in Polish population (Dubaniewicz et al, 2005), but a negative association in the Sahariya tribe of North Central India (Mishra et al, 2014). DRB1*12 has been reported in the Indonesian population (Yuliwulandari et al, 2010), DRB1*13 in the Polish (Dubaniewicz et al, 2000), and South African populations (Lombard Z et al, 2006), and DRB1*14 in the Iranian (Mahmoudzadeh et al, 2003) and Portuguese populations (Duarte et al, 2011). The differences in the HLA-DRB alleles between the populations can be partly explained by the variation in the technique used, limited sample size and linkage disequilibrium.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…DRB1*16 is reported to have a positive association with the susceptibility to tuberculosis in Polish population (Dubaniewicz et al, 2005), but a negative association in the Sahariya tribe of North Central India (Mishra et al, 2014). DRB1*12 has been reported in the Indonesian population (Yuliwulandari et al, 2010), DRB1*13 in the Polish (Dubaniewicz et al, 2000), and South African populations (Lombard Z et al, 2006), and DRB1*14 in the Iranian (Mahmoudzadeh et al, 2003) and Portuguese populations (Duarte et al, 2011). The differences in the HLA-DRB alleles between the populations can be partly explained by the variation in the technique used, limited sample size and linkage disequilibrium.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have identified a positive association between the DRB1 alleles and TB across geographical locations-DRB1*15 in the Sahariya tribe (Mishra et al, 2014), DRB1*0801 and DRB1*0803 in Kazakhstan (Kuranov et al, 2014), DRB1*15 in Chinese (Shi et al, 2011), DRB1*14 in Portuguese (Duarte et al, 2011), DRB1*0803 in Korean (Kim et al, 2005), DRB1*16 in Polish (Dubaniewicz et al, 2000), DRB1*04 and DRB1*11 in Syrian (Harfouch and Daher, 2008), and DRB1*07 in Iranian populations (Amirzargar et al, 2004). However, other studies have reported no association.…”
Section: Introductionmentioning
confidence: 99%
“…HLA-DR2 is divided into two subtypes, DRB1*15 and DRB*16. Except for the study reported by Dubaniewicz and his colleagues, DRB1*15, especially the DRB1*1501 allele, is strongly associated with PTB susceptibility (Dubaniewicz et al, 2000). This observation suggests that amino acids present in DR15 molecule but absent in DR16 could play an important role in the development of PTB.…”
Section: Mhc Polymorphism and Tb Diseasementioning
confidence: 76%
“…Finally, HLA-DR2 seems to be the main allele positively associated with PTB. This observation is replicated in populations with different genetic background, Indian (Brahmajothi et al, 1991, Ravikumar et al, 1999, Sriram et al, 2001, Chinese (Shi et al, 2011) and polish (Dubaniewicz et al, 2000). HLA-DR2 is divided into two subtypes, DRB1*15 and DRB*16.…”
Section: Mhc Polymorphism and Tb Diseasementioning
confidence: 81%
“…107 The HLA Class II variant, DR2 encoded by DRB1*15 and DRB1*16, is associated with TB in several populations. 108,109 A meta analysis study reported that subjects carrying HLA-B13 had a lower risk for thoracic TB, whereas other Class I antigens could not be related to tuberculosis pathogenesis. 110 Furthermore, HLA-DRB1*04 and HLA-DQB1*02:01 were associated with TB in Chinese patients.…”
Section: Hla and Mycobacterium Tuberculosis Infectionmentioning
confidence: 99%